2013
DOI: 10.1002/jwmg.600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two porcine zona pellucida immunocontraceptive vaccines on ovarian activity in horses

Abstract: Feral horse population growth rates as high as 25% are of concern to those responsible for managing range lands as well as conservation groups. Current methods to control these populations include adoption and long-term holding, which are both costly and controversial. Porcine zona pellucida (pZP) immunocontraception may have the greatest potential to control fertility because it has proven to be effective in other studies and vaccines are easy and safe to administer. One pZP vaccine formulation, SpayVac 1 (Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 68 publications
(119 reference statements)
5
32
6
Order By: Relevance
“…The current study, however, demonstrated suppression of ovarian function in 6 of 7 pony mares following pZP treatment, characterised by small, Equine Veterinary Journal 49 (2017) 189-195 © 2015 EVJ Ltd inactive ovaries and basal ovarian hormone levels. Our findings confirm recently reported ovarian quiescence in mares treated with long-acting pZP vaccines [13], suggesting that suppressed ovarian function is not unique to long-acting formulations. Our findings confirm recently reported ovarian quiescence in mares treated with long-acting pZP vaccines [13], suggesting that suppressed ovarian function is not unique to long-acting formulations.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The current study, however, demonstrated suppression of ovarian function in 6 of 7 pony mares following pZP treatment, characterised by small, Equine Veterinary Journal 49 (2017) 189-195 © 2015 EVJ Ltd inactive ovaries and basal ovarian hormone levels. Our findings confirm recently reported ovarian quiescence in mares treated with long-acting pZP vaccines [13], suggesting that suppressed ovarian function is not unique to long-acting formulations. Our findings confirm recently reported ovarian quiescence in mares treated with long-acting pZP vaccines [13], suggesting that suppressed ovarian function is not unique to long-acting formulations.…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancy between our findings and that of an earlier report of unaltered oestrous cyclicity during short-term treatment of mares with conventional pZP vaccine [1] may be due to the higher pZP dose administered in our study (100 lg vs. 65 lg pZP), selected to reflect the current dose administered to feral horses [24][25][26]. Our findings confirm recently reported ovarian quiescence in mares treated with long-acting pZP vaccines [13], suggesting that suppressed ovarian function is not unique to long-acting formulations.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations